Comparison of NICE and ESC proposed strategies on new onset chest pain and the contemporary clinical utility of pretest probability risk score. Issue 1 (27th May 2020) - Papachristidis, Alexandros; Vaughan, George Frederick; Denny, Sarah J; Akbari, Tamim; Avornyo, Edith; Griffiths, Tracey; Saunders, Emma; Byrne, Jonathan; Monaghan, Mark J; Al Fakih, Khaled
Abstract : Aims: Patients with de novo chest pain are usually investigated non-invasively. The new UK-National Institute for Health and Care Excellence (NICE) guidelines recommend CT coronary angiography (CTCA) for all patients, while European Society of Cardiology (ESC) recommends functional tests. We sought to compare the clinical utility and perform a cost analysis of these recommendations in two UK centres with different primary investigative strategies. Methods—results: We compared two groups of patients, group A (n=667) and group B (n=654), with new onset chest pain in two neighbouring National Health Service hospitals, each primarily following either ESC (group A) or NICE (group B) guidance. We assessed the clinical utility of each strategy, including progression to invasive coronary angiography (ICA) and revascularisation. We present a retrospective cost analysis in the context of UK tariff for stress echo (£176), CTCA (£220) and ICA (£1001). Finally, we sought to identify predictors of revascularisation in the whole population. Baseline characteristics in both groups were similar. The progression to ICA was comparable (9.9% vs 12.0%, p=0.377), with similar requirement for revascularisation (4.0% vs 5.0%.; p=0.532). The average cost of investigations per investigated patient was lower in group A (£279.66 vs £325.77), saving £46.11 per patient. The ESC recommended risk score (RS) was found to be the only predictor of revascularisation (OR 1.05, 95% CI 1.04 to 1.06; p<0.001). Conclusion: Both NICE and ESC-proposed strategies led to similar rates of ICA and need for revascularisation in discrete, but similar groups of patients. The SE-first approach had a lower overall cost by £46.11 per patient, and the ESC RS was the only variable correlated to revascularisation.